Study of the Effect of Panax Ginseng versus Gliclazide on Hyperglycaemia Induced by Dexamethasone in Experimental Animals - Ibrahim, Doa'a A. (Sultan Qaboos University, 2009)
Objectives: To study the effect of panax ginseng versus gliclazide on hyperglycaemia induced by dexamethasone in experimental animals. Methods: The current study was conducted in the Department of Pharmacology, University of Science & Technology, Sana’a, Yemen. Twenty-four rabbits were divided to 4 groups. Three of them were administered oral doses of dexamethasone (10 mg/kg) for 14 days, one group was kept as a control. Ginseng at dose (200 mg/kg) and gliclazide (80 mg/kg) were administered to rabbits with dexamethasone-induced hyperglycaemia. Results: The effects of ginseng and gliclazide on fasting blood sugar (FBS) and body weight after continuous administration of dexamethasone (10 mg/kg) were measured. Oral administration of ginseng (200mg/kg) for 2 weeks produced significant (p < 0.05) reduction in FBS from 215.33±27.67 mg/dl in the dexamethasone group to 154.17±21.18mg/dl in the ginseng treated group. In addition, ginseng produced significant (p < 0.05) reduction in body weight. Conclusion:There was a significant difference between ginseng and gliclazide in reduction of FBS and body weight. From these results, it is suggested that ginseng could be used in obese diabetic patients or those suffering from insulin resistance as it reduces body weight.